New Social Movements in Mental Health Issues: The Role of Griya Schizofren in Humanizing People with Mental Health Problems (ODMK) in Surakarta City - Hapsari, Yuanita Dwi; Rahmawati , Triana; Kurniawan , Deni Aries; Hikmat, Rohman (Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Stigma against People with Mental Disorders (ODGJ) and People with Mental Health Problems (ODMK) remains a major obstacle to psychosocial recovery and community integration. This study examines the role of Griya Schizofren in Surakarta as a community-based social movement in empowering individuals with mental health challenges. A qualitative research method was employed using a case study approach through in-depth interviews, participatory observation, and document analysis. The findings reveal that Griya Schizofren implements routine activities and mentoring programs, such as Fruit Day and Art Day, which create safe spaces for psychosocial recovery while fostering positive identities and egalitarian social relations. In addition, creative economic initiatives through the social entrepreneurship program Solvenesia generate both economic and social impacts beyond therapy, strengthening survivors’ social identity and serving as a form of advocacy for the recognition of the rights of ODMK and ODGJ. The strategy of social media outreach and cross-sector collaboration can broaden the reach of advocacy efforts and enhance public legitimacy. The study concludes that Griya Schizofren functions not merely as a support institution but as a New Social Movement that articulates resistance against stigma and marginalization through community-based practices. These findings highlight the importance of a holistic approach that integrates psychosocial, economic, and sociocultural dimensions within mental health movements, while also enriching theoretical discussions on the dynamics of New Social Movements in Indonesia.